Insuficiencia renal crónica y su incidencia en la salud mental de un paciente adulto de 32 años de la Unidad de Hemodiálisis del Cantón Vinces - Pionce Mendoza, Adriana Michel (2023)
In this study, we conducted research on chronic renal insufficiency and its impact on the mental health of a 32-year-old patient. As a result, I know that patients with kidney disease may have difficulties in mental health leaving unpleasant scars in the personal life of the sufferer. In perspective, a psychotherapeutic intervention was performed with an approach of cognitive behavioral technique, with the purpose of restructuring their cognitive processes that are harming their behavior patterns, It should be noted that this psychotherapeutic technique supported psychometric tests and each of the sessions was able to discover that the patient showed an anxious picture, for this reason this situation were influencing his personal life. With different techniques, we managed to address the current situation that the patient lives, interfering in their thought processes and mental health, with the aim of improving the quality of life and that this is reflected in interpersonal relationships for a better social psychological well-being